Contribution à l'épigraphie et à l'histoire de la Béotie hellénistique De la destruction de Thèbes à la bataille de Pydna - Kalliontzis, Yannis (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2020)
This study offers the first synthesis in French of the history of the Boeotian confederacy in the Hellenistic period, from the destruction of Thebes by Alexander the Great (335 BC) to the battle of Pydna and its immediate consequences in Boeotia (168-167 BC). The Boeotian confederacy, one of the oldest in the Greek world, played an important role in the history of Greece during the Hellenistic period. An analysis of the sources, notably epigraphic, sheds new light on whole swathes of the political, institutional, economic and social history of this unique political system. The originality and relevance of this research is also due to the key contribution of new inscriptions, published for the first time in a scientific work with an in-depth commentary. Through its rigor and breadth of perspective, this research hopes to encourage studies on Boeotia, but also more broadly on ancient federalism, an original political experience which remains an important source of inspiration in Europe. It also constitutes part of a series of regional studies that lay out an important path to further our knowledge of Greek history. Yannis Kalliontzis, former member of the École française d'Athènes, is a historian and epigraphist. Trained in Greece, Switzerland and France, he studied the epigraphy and history of several regions of Greece. He is currently working on a new edition of the corpus of inscriptions from Boeotia, to appear in the Academy of Berlin's Inscriptiones Graecae series.